Food Security and Wildlife Management in Nunavut - Lysenko, D. (Dmitry); Schott, S. (Stephan) (Ecological Economics, 2019)
The purpose of our study is to examine important dimensions of food security in the context of current wildlife management in Nunavut, Canada. In doing so, we attempt to bridge harvesting studies and food security studies. The latter have been primarily focused on household food affordability, which is not adequate in the predominantly indigenous areas of the Arctic. We presume that one of the appropriate levels at which food security can be meaningfully measured is the community level because households within communities are closely connected by sharing networks and because data on many dimensions of food security are publicly available at that level. We explore several important dimensions of food security looking at the composition of communities in terms of households with different income, employment, and demographic characteristics, and at the scope of harvesting by hunters in communities. Based on this analysis, we identify communities with relatively high and low levels of food security and discuss implications of our analysis for wildlife management in Nunavut that may also be useful for other indigenous areas of the Arctic.